2022
DOI: 10.1002/hyp.14705
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the effect of simulated grass and stem coverage on resistance coefficient of overland flow

Abstract: Vegetation plays a significant role in preventing desertification, conservation of soil and water. However, nowadays, there is still uncertainty regarding the mechanisms of flow resistance caused by dissimilar vegetation covers. To address this gap, a series of these was conducted in this study to investigate the influence of synthetic grass and stems on the variation of resistance on overland flows. Thirty vegetation configurations were selected (combining five synthetic grass coverage options and six synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…This may be why the equation of Langridge et al (2021), which includes representations of the climate and the peak discharge, performed relatively well in this study. Cen et al (2022) found that unit discharge was the most important factor in determining the transition from laminar to transitional flows, in flume experiments using synthetic vegetation.…”
Section: Darcy-weisbach Roughness Coefficient Fmentioning
confidence: 97%
“…This may be why the equation of Langridge et al (2021), which includes representations of the climate and the peak discharge, performed relatively well in this study. Cen et al (2022) found that unit discharge was the most important factor in determining the transition from laminar to transitional flows, in flume experiments using synthetic vegetation.…”
Section: Darcy-weisbach Roughness Coefficient Fmentioning
confidence: 97%
“…Vegetation characteristics such as shape, stiffness, degree of submergence, and arrangement, in uence the hydrodynamic properties of slope ow [20]. Cen et al [21] studied the hydrodynamic properties of slope ow under combinations of exible and rigid vegetation and found that different types of vegetation can differentially affect ow resistance. Serio et al [20] also studied the hydraulic characteristics of owing rivers under the in uence of rigid and exible vegetation and found that the density and rigidity of vegetation affected the spatiotemporal distribution of the average ow velocity to different degrees.…”
Section: Introductionmentioning
confidence: 99%
“…Teng et al [23] reported that the distribution of ow velocity under different arrangements of rigid vegetation was lower close to the channel bottom and in the inner layers of the vegetation, with ow velocities along the water depth displaying S-shaped and inverse S-shaped pro les. Most simulation studies on vegetation set the growth direction of vegetation perpendicular to the slope (BS) [21,24,25]; however, in nature, vegetation can also grow perpendicular to the horizontal plane (BH). As there is little research that focuses on the effects of vegetation growth direction on average ow velocity, the impacts of these two types of vegetation on slope ow velocity must be measured independently.…”
Section: Introductionmentioning
confidence: 99%